Integrated Evaluation of the Performance of Composite Cool Thermal Insulation Materials. (November 2015) - Antoniadou, P.; Giama, E.; Boemi, S.-N.; Karlessi, Th.; Santamouris, M.; Papadopoulos, A.M.
Abstract: A family of composite cool thermal insulation materials has been developed as part of the DICOM research project, in order to provide building materials optimized for the retrospective insulation of existing buildings, which contribute in particular to the reduction of cooling loads in summer. An integrated evaluation of the materials was carried out in 2013-2014, by means of in vitro and in situ measurements, in order to determine and evaluate the materials' performance and the thermal comfort conditions before and after the retrofitting. Finally, a Life Cycle Analysis was carried for the materials, in order to evaluate their environmental impact.